The impact of multimedia on teaching tropical medicine - Sarmento E Souza, M. F. [UNESP]; Ferreira, A. S. S. B.; Martinez, J. C. [UNESP]; Barraviera, B. [UNESP] (Centro de Estudos de Venenos e Animais Peçonhentos, 2004)
This study evaluated the impact of multimedia in the information transfer of subjects specific to Tropical Diseases - Tetanus and Snake Envenoming. We evaluated the autonomous learning process of 76 fourth-year medical students at Botucatu School of Medicine of UNESP, using printed matter, video, and CD-ROM. The students were submitted to a specific test, which was repeated approximately one week later. They were divided into groups and received a kit containing a textbook, a video, and a CD-ROM. These materials were used for out-of-class study. Before the second test, the students gave a seminar,where they discussed and resolved their doubts with their professor. The results of the first test showed averagesbetween 4.27±1.41 and 6.41±1.61. The second test, given after the seminar, presented averages that increased to 8.41±0.76 and 9.52±0.42, significance a = 5%. At the end of the course, the students answered a questionnaire, which evaluated the material quality and acquired knowledge. The students concluded that multimedia was a more efficient and quick means for knowledge building than traditional teaching materials. They said that the active participation and interactivity with the CD-ROM were the major differences. The authors continue to study the associated use of printed matter, video, and CD-ROM as a faster alternative to the traditional method of information transfer, which may be of help in the knowledge building process in medical education.
Keywords: Medical education; tropical diseases; multimedia; video; printed matter